Caesalpinia sappan Linn. Ameliorates Allergic Nasal Inflammation by Upregulating the Keap1/Nrf2/HO-1 Pathway in an Allergic Rhinitis Mouse Model and Nasal Epithelial Cells - Bo-Jeong Pyun; Kyuhyung Jo; Joo Young Lee; Ami Lee; Myung-A Jung; Youn-Hwan Hwang; Dong Ho Jung; Kon-Young Ji; Susanna Choi; Yun Hee Kim; Taesoo Kim (Antioxidants, 2022)
Allergic rhinitis (AR) is a common upper-airway inflammatory disease of the nasal mucosa caused by immunoglobulin (IgE)-mediated inflammation. AR causes various painful clinical symptoms of the nasal mucosa that worsen the quality of daily life, necessitating the urgent development of therapeutic agents. Herein, we investigated the effects of Caesalpinia sappan Linn. heartwood water extract (CSLW), which has anti-inflammatory and antioxidant properties, on AR-related inflammatory responses. We examined the anti-inflammatory and anti-allergic effects of CSLW in ovalbumin (OVA)-induced AR mice and in primary human nasal epithelial cells (HNEpCs). Administration of CSLW mitigated allergic nasal symptoms in AR mice, decreased total immune cell and eosinophil counts in nasal lavage fluid, and significantly reduced serum levels of OVA-specific IgE, histamine, and Th2 inflammation-related cytokines. CSLW also inhibited the infiltration of several inflammatory and goblet cells, thereby ameliorating OVA-induced thickening of the nasal mucosa tissue. We found that CSLW treatment significantly reduced infiltration of eosinophils and production of periostin, MUC5AC, and intracellular reactive oxygen species through the Keap1/Nrf2/HO-1 pathway in HNEpCs. Thus, our findings strongly indicate that CSLW is a potent therapeutic agent for AR and can improve the daily life of patients by controlling the allergic inflammatory reaction of the nasal epithelium.